In-situ synthesis of well dispersed CoP nanoparticles modified CdS nanorods composite with boosted performance for photocatalytic hydrogen evolution. (9th August 2018) - Wang, Junfang; Wang, Peifang; Wang, Chao; Ao, Yanhui
Abstract: Development of photocatalysts with characters of low-cost, environment friendliness, visible light response and good performance is vital for the transformation of solar energy into hydrogen fuel. Here, we constructed CoPCdS nanorods hybrid composites via a novel two-step in-situ growth method for the first time. The obtained CoPCdS composites exhibited remarkably enhanced photocatalytic performance and excellent stability in comparison with bare CdS nanorods. Notably, the optimum H2 evolution rate of 1 wt%CoPCdS was 9.11 times higher than that of pristine CdS. The apparent quantum efficiency of the photocatalyst was calculated to be 11.6%. The superior activity of this material could be attributed to the role of well dispersed CoP nanoparticles and the intimate interface between CoP cocatalysts and CdS nanorods, which efficiently accelerated the separation and transfer of photogenerated electrons. This work provided a new in-situ growth method for the preparation of transition metal phosphides coated photocatalysts with boosted photocatalytic activity of hydrogen evolution. Highlights: CoP/CdS composites were prepared via a in-situ growth method for the first time. The composites exhibited greatly enhanced photocatalytic hydrogen evolution rate. Well dispersion and intimate interface between CoP and CdS nanorods contributed to the high activity.